How Entrepreneurship Education, Social Media, and Business Capital Shape Gen Z Entrepreneurial Intentions through Income Expectations? - Hajar Dewantara; Andi Anggi Kemalasari; Atirah; Matthew Olufemi Adio (PT Mattawang Mediatama Solution, 2025)
The advancement of digital technology encourages transformation in various fields. This research aims to analyze the influence of entrepreneurship education, social media, and business capital on the entrepreneurial interest of Generation Z through income expectations as a mediating variable. This study employs a quantitative approach with descriptive and explanatory designs. The sample consists of 106 students from the Universitas Negeri Makassar selected through proportional random sampling techniques. Data collection was conducted using a Likert scale-based questionnaire and analyzed using path analysis with the help of SPSS software. The results indicate that entrepreneurship education, social media, and business capital significantly influence income expectations and the entrepreneurial interest of Generation Z. Directly, business capital has the greatest impact on entrepreneurial interest. Furthermore, income expectations prove to be a significant mediating variable that strengthens the relationship between entrepreneurship education, social media, and business capital on entrepreneurial interest. This study emphasizes the importance of practice-based entrepreneurship education, optimal utilization of social media, and adequate access to business capital to encourage Generation Z to become entrepreneurs. Income expectations play a key role in motivating students to start and develop businesses.